2019
DOI: 10.1109/access.2019.2955167
|View full text |Cite
|
Sign up to set email alerts
|

Space Charge Behavior in Ethylene Propylene Rubber Under a 50-Hz AC Electric Field

Abstract: In this study, the space charge behavior in ethylene propylene rubber (EPR) under a 50-Hz AC field is studied based on the variation of space charge response, FTIR spectra and impurity contents inside EPR with thermal treatment. The space charge was detected with the pulsed electroacoustic (PEA) method and the phase shift of detecting pulse under 50 Hz AC field was realized according to the automatic equal phase shift (AEPS) principle. The results show three main types of impurities in untreated EPR. Three dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…It can be seen that the electric field in the material is significantly distorted, where the field inside the sample is enhanced and the field near the electrode is weakened. The distortion rate δ of electric field is applied to characterize the changing of electric field as follows [21]: δbulk=EmaxEavEavδel=EavEminEav. where the E max is the maximum value of electric field inside the sample, E min is the minimum value of electric field near the electrode and E av is the ideal average electric field. Due to the significant injection of electron in cathode, the δ el near cathode and δ bulk inside the material are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It can be seen that the electric field in the material is significantly distorted, where the field inside the sample is enhanced and the field near the electrode is weakened. The distortion rate δ of electric field is applied to characterize the changing of electric field as follows [21]: δbulk=EmaxEavEavδel=EavEminEav. where the E max is the maximum value of electric field inside the sample, E min is the minimum value of electric field near the electrode and E av is the ideal average electric field. Due to the significant injection of electron in cathode, the δ el near cathode and δ bulk inside the material are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…It can be seen that the electric field in the material is significantly distorted, where the field inside the sample is enhanced and the field near the electrode is weakened. The distortion rate δ of electric field is applied to characterize the changing of electric field as follows [21]:…”
Section: Space Charge and Electric Field Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been widely utilized in the traditional measurement environments including DC and AC voltages within power frequency. For the researches on the same insulating material, it has been found that different voltage conditions can lead to different charge accumulation phenomena [13,14]. Moreover, since the injection barriers and the mobilities of electrons and holes from the electrodes are different, the polarity of applied voltages can also affect the charge distributions inside the same samples [15].…”
Section: Introductionmentioning
confidence: 99%